Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery

By adjusting the crystal structure factor A of the lithium iron phosphate positive electrode material and using a carbon cladding layer, the problem of insufficient electrochemical performance in low temperature environments is solved, and excellent low-temperature electrochemical performance and conductivity are achieved.

CN119230801AActive Publication Date: 2024-12-31GUANGDONG BRUNP RECYCLING TECH CO LTD

Patent Information

Application Number
CN202411719686.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-31
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The lithium iron phosphate positive electrode material has low lithium ion diffusion rate and conductivity under low temperature environments, resulting in poor electrochemical performance of its batteries under low temperature conditions. The existing technology mainly relies on the installation of self-heating systems rather than the improvement of amorphous structure. .

Method used

By adjusting the crystal structure factor A of the lithium iron phosphate positive electrode material, ensure that it is within the range of 4.600-4≤A≤9.500-4, and combined with the use of carbon cladding, the crystallinity, unit cell volume and grain size are optimized, so as to Improve low-temperature electrochemical properties.

Benefits of technology

The excellent electrochemical performance of lithium iron phosphate positive electrode material under low temperature conditions is achieved, including improving the diffusion rate and conductivity of lithium ions, extending battery life and improving cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230801A_ABST
    Figure CN119230801A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery, and relates to the technical field of positive electrode materials. The lithium iron phosphate positive electrode material comprises a matrix and a carbon coating layer coated on the surface of the matrix, the crystal structure factor A of the lithium iron phosphate positive electrode material meets 4.600 # imgabs0 #-4 < = A < = 9.500 # imgabs1 #-4, and the calculation formula of the crystal structure factor A is A = # imgabs2 #; wherein C is the crystallinity of the crystal; v refers to unit cell volume; # imgabs3 is the grain size of the crystal face # imgabs4 #, and the value meets the condition that # imgabs6 # is larger than or equal to 4 # imgabs5 # and smaller than or equal to 9 # imgabs7 #. The lithium iron phosphate positive electrode material in the range has excellent low-temperature electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium iron phosphate is one of the most competitive cathode active materials for lithium-ion batteries on the market. Compared with lithium cobalt oxide and ternary cathode materials, it has a longer life and better safety performance. In addition, lithium iron phosphate has a capacity of 170mAh g -1 Theoretical specific capacity and platform discharge voltage of 3.4V make it have considerable energy density.

[0003] LiFePO4 has an olivine structure and its space group is Pbnm. In the LiFePO4 crystal, O atoms are arranged in a slightly twisted hexagonal close-packed manner. P atoms occupy the 4c ​​position of the O atom tetrahedron to form a PO4 tetrahedron. Fe and Li are located at the center of the oxygen atom octahedron to form FeO6 and LiO6 octahedrons. On the bc plane, adjacent FeO6 octahedra share one oxygen atom, thus linking to each other to form a zigzag FeO6 layer. Between the FeO6 layers, adjacent LiO6 octahedra are linked by two oxygen atoms in the b direction, forming a continuous straight chain of Li parallel to the c axis, which makes Li + It is possible to form a two-dimensional diffusion movement. From a structural point of view, the PO4 tetrahedron is located between the FeO6 layers, which hinders the Li + At the same time, the adjacent FeO6 octahedrons are connected by common vertices, and no octahedral structure with common edges is formed, which makes its conductivity very low. Furthermore, due to the above crystal configuration of LiFePO4, its capacity and rate performance in low temperature environment are worse than those of ternary positive electrode material batteries, because Li + The chemical reactions for deintercalation are more difficult to carry out.

[0004] In order to improve the lithium ion diffusion rate and conductivity of LiFePO4, the existing technology has conducted a lot of research on LiFePO4 nano-crystallization and carbon coating. In order to improve the low-temperature serviceability of lithium iron phosphate batteries, the current commercial solution is to install a self-heating system on the power unit to keep the battery warm or heat it, but there are few research reports on adjusting the crystal structure of LiFePO4 to improve the low-temperature electrochemical performance of LiFePO4 batteries.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a lithium iron phosphate positive electrode material and a preparation method thereof and a lithium ion battery.

[0007] The present invention is achieved in that: In a first aspect, the present invention provides a lithium iron phosphate positive electrode material, which comprises a substrate and a carbon coating layer coated on the surface of the substrate, wherein the crystal structure factor A of the lithium iron phosphate positive electrode material satisfies 4.600 -4 ≤A≤9.500 -4 , the calculation formula of the crystal structure factor A is: A= ; Wherein, C refers to the crystallinity of the lithium iron phosphate positive electrode material, which is measured by the ratio of the XRD diffraction peak intensity of the crystal plane (311) to the integrated area of ​​the diffraction peak; V refers to the unit cell volume of the lithium iron phosphate positive electrode material, unit 3 ; Refers to the crystal surface of the lithium iron phosphate positive electrode material The grain size, unit , the value satisfies 4 ≤ ≤9 .

[0008] In an optional embodiment, the lithium iron phosphate positive electrode material satisfies at least one of the following characteristics (1) to (3): Feature (1): The value satisfies 4 ≤ ≤6 ; Feature (2): The value of C satisfies 0.0900≤C≤0.1200; Feature (3): The value of V satisfies 290 ≤V≤292 .

[0009] In an optional embodiment, the general formula of the matrix is ​​as follows: Li 1-x A x Fe 1-y M y (PO 4-z )D z , wherein A is selected from at least one of Na and Mg; M is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; D is selected from at least one of F, S, N and Cl; 0≤x≤0.1; 0≤y≤0.1 and 0≤z≤0.1.

[0010] In an optional embodiment, the mass of the carbon coating layer is 0.5% to 5% of the mass of the lithium iron phosphate positive electrode material.

[0011] In a second aspect, the present invention provides a method for preparing a lithium iron phosphate positive electrode material, comprising: Stirring a mixture of lithium carbonate, a divalent iron source, a phosphorus source and an ethylene glycol compound solution to react to obtain a precursor suspension; The precursor suspension is subjected to a hydrothermal reaction and solid-liquid separation to obtain a solid precursor; The solid precursor and the carbon source are mixed and dried, and then calcined under an inert atmosphere to obtain a lithium iron phosphate positive electrode material.

[0012] In an optional embodiment, the process of preparing the precursor suspension includes at least one of the features (4) to (9): Feature (4): The divalent iron source is selected from at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous oxalate and ferrous acetate; Feature (5): The phosphorus source is at least one selected from phosphoric acid, sodium dihydrogen phosphate, sodium monohydrogen phosphate, ammonium dihydrogen phosphate and ammonium monohydrogen phosphate; Feature (6): The mass percentage content of the ethylene glycol compound in the ethylene glycol compound solution is 5% to 20%; Feature (7): The ethylene glycol compound refers to a water-soluble compound containing an ethylene glycol structure, and the ethylene glycol compound is selected from at least one of 1,2-ethylene glycol, squaric acid, crotonic acid, sodium crotonate, 2,3-dihydroxycyclopent-2-ene-1-one, 2,3-dihydroxy-4-(hydroxymethyl)cyclopent-2-ene-1-one and 3,4-dihydroxy-5-methyl-2-furanone; Feature (8): The pH of the solution in the stirring reaction is 1-2.5, the reaction temperature is 80-90°C, the reaction time is 1-4h, and the stirring speed is 300-800rpm; Feature (9): After the stirring reaction is completed, the temperature is lowered to 10-25°C and stirred until no bubbles are generated.

[0013] In an optional embodiment, an M source is also added during the preparation of the mixture, which includes at least one of the characteristics (10) to (13): Feature (10): dissolving the divalent iron source and the M source in the ethylene glycol compound solution to form a metal salt solution, dissolving the phosphorus source in water to form a phosphorus source solution; dispersing the lithium carbonate in the metal salt solution to obtain a dispersion, and then adding the phosphorus source solution to obtain the mixture, wherein the molar concentration of the metal element in the metal salt solution is 0.8~1.5M, and the molar concentration of the phosphorus source in the phosphorus source solution is 0.85~3M; Feature (11): The ratio of the total molar amount of the divalent iron source and the M source to the molar amount of the phosphorus source is 1:1.05-1.5; Feature (12): The ratio of the total molar amount of the divalent iron source and the M source to the molar amount of the lithium element in the lithium carbonate is 1:1.01-1.1; Feature (13): The M source includes a water-soluble salt of at least one element selected from the group consisting of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y.

[0014] In an optional embodiment, the conditions of the hydrothermal reaction in the process of preparing the solid precursor are: temperature of 160-200° C., time of 1-3 h, and stirring rate of 100-300 rpm.

[0015] In an optional embodiment, after the solid precursor and the carbon source are mixed and dried, the process of calcining under an inert atmosphere includes at least one of the features (14) to (17): Feature (14): The mass ratio of the solid precursor to the carbon source is 1:0.04-0.1; Feature (15): The carbon source is selected from at least one of glucose, starch, phenolic resin, sucrose, cellulose, polyethylene glycol and citric acid; Feature (16): The mixing process further includes adding a source A and / or a source D, wherein the source A is selected from at least one of magnesium fluoride, sodium fluoride, sodium chloride and sodium sulfide; and the source D is selected from at least one of potassium fluoride, magnesium fluoride, sodium fluoride, ammonium fluoride, lithium fluoride, melamine, amino acid, thiocyanate, thiourea, elemental sulfur, sodium sulfide, ammonium sulfide, sodium chloride, ammonium chloride, lithium chloride and urea; Feature (17): The calcination includes calcination at 550-650°C for 4-8 hours.

[0016] In a third aspect, a lithium-ion battery comprises the lithium iron phosphate positive electrode material as described in any one of the aforementioned embodiments or the lithium iron phosphate positive electrode material prepared by the method for preparing the lithium iron phosphate positive electrode material as described in any one of the aforementioned embodiments.

[0017] The present invention has the following beneficial effects: (1) The present invention provides a lithium iron phosphate positive electrode material, the crystal structure factor A of which satisfies 4.600 -4 ≤A≤9.500 -4 , while its grain size Meet 4 ≤ ≤9 The lithium iron phosphate cathode material that meets the above range has excellent low-temperature electrochemical performance. The crystal structure factor comprehensively evaluates the crystallinity C, unit cell volume V and crystal surface of the lithium iron phosphate cathode material. The grain size Three indicators. Among them, the higher the crystallinity C, the fewer internal defects in the material, and the higher the lithium ion diffusion rate; the smaller the unit cell volume, the shorter the lithium ion deintercalation channel, the easier it is to transition, which is beneficial to improving the cycle performance; the smaller D(010), the more conducive to shortening the lithium ion diffusion channel, improving the charge and discharge specific capacity and rate performance; crystallinity C, unit cell volume V, grain size Each of them has an impact on the performance of the lithium iron phosphate positive electrode material, but it is actually difficult to obtain a positive electrode material that is superior in all three aspects. Therefore, the present invention provides a crystal structure factor A that comprehensively evaluates the three aspects of the lithium iron phosphate positive electrode material, which has a crystal structure factor A that meets 4.600 -4 ≤A≤9.500 -4 , while satisfying 4 ≤ ≤9 The lithium iron phosphate positive electrode material has excellent low-temperature electrochemical properties.

[0018] (2) The method for preparing the lithium iron phosphate positive electrode material provided by the present invention can prepare a lithium iron phosphate positive electrode material having a D(010) in the preferred range (4 ~6 ), lithium iron phosphate positive electrode material with high crystallinity. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 A schematic diagram showing the comparison of XRD of lithium iron phosphate positive electrode materials prepared in Example 3, Example 5, Comparative Example 1 and Comparative Example 2 of the present invention with a standard card; Figure 2 SEM images of lithium iron phosphate positive electrode materials prepared in Example 3 (A) of the present invention and Comparative Example 1 (B). DETAILED DESCRIPTION

[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0022] The present invention provides a lithium iron phosphate positive electrode material, which includes a substrate and a carbon coating layer coated on the surface of the substrate, and the crystal structure factor A of the lithium iron phosphate positive electrode material satisfies 4.600 -4 ≤A≤9.500 -4 , the calculation formula of the crystal structure factor A is: A= ; Wherein, C refers to the crystallinity of lithium iron phosphate cathode material, which is measured by the ratio of the XRD diffraction peak intensity of the crystal plane (311) to the integrated area of ​​the diffraction peak; V refers to the unit cell volume of lithium iron phosphate cathode material, unit 3 ; Refers to the crystal surface of lithium iron phosphate positive electrode material The grain size, unit , the value satisfies 4 ≤D(010)≤9 .

[0023] The present invention uses lithium iron phosphate positive electrode material as a sample to perform X-ray diffraction (XRD) test on it, and uses JADE software to deduct Cu K 2 background, the XRD spectrum is obtained after full spectrum fitting and refinement; the crystallinity C, unit cell volume V and D(010) are obtained through the XRD spectrum, and the crystal structure factor A is calculated, and the crystal structure factor A is screened to meet the value of 4.600 -4 ≤A≤9.500 -4 , and its grain size D(010) satisfies 4 ≤D(010)≤9 The sample is used as the lithium iron phosphate positive electrode material of the present invention. The lithium iron phosphate positive electrode material that meets the above range has excellent low-temperature electrochemical properties.

[0024] Among them, C refers to the crystallinity of the lithium iron phosphate positive electrode material. The crystallinity C of the lithium iron phosphate positive electrode material is measured by the ratio of the diffraction peak intensity of the diffraction peak with the largest peak intensity ((311) crystal plane) in the XRD spectrum to the integrated area of ​​the diffraction peak, and the corresponding 2θ=34.8~35.8°.

[0025] Furthermore, the diffraction peak intensity and the integrated area of ​​the diffraction peak can reflect the sharpness of the diffraction peak. The smaller the integrated area at the same intensity, the sharper the diffraction peak; similarly, the stronger the peak intensity at the same integrated area, the sharper the diffraction peak; the sharper the diffraction peak, the higher the crystallinity; the higher the crystallinity, the higher the lithium ion diffusion rate and the better the conductivity. The value of C satisfies 0.0900≤C≤0.1200. Theoretically, the larger the C, the better, but 0.12 is the maximum value that can be obtained by the present invention.

[0026] V refers to the unit cell volume of lithium iron phosphate positive electrode material. Unit cell is the basic unit of crystal structure, which describes the arrangement of atoms or molecules in the crystal. The smaller the unit cell volume, the shorter the lithium ion deintercalation channel and the easier it is to transition, which is beneficial to improve the conductivity of the material and improve the cycle performance. The unit cell volume is generally related to the crystal form and chemical composition. The V value meets 290 ≤V≤292 , a unit cell volume that is too small will lead to poor structural stability of the positive electrode material and decreased cycle performance.

[0027] D(010) refers to the grain size of the crystal plane (010) of the lithium iron phosphate positive electrode material, unit is in accordance with The diffraction angle of the crystal plane ( ) and the half-width of the diffraction peak ( ) and calculated according to the Scherrer formula: ; k is a constant value, the value is 0.9; is the wavelength of the incident ray; It refers to the half-peak width of the diffraction peak, and its unit is rad; Refers to the diffraction angle, unit is °. The grain size can reflect the macroscopic size of the crystal, because D = nd, d refers to the interplanar spacing of the crystal plane, and n refers to the number of crystal layers; the smaller D (010) is, the fewer the number of crystal layers corresponding to the crystal plane or / and the smaller the interplanar spacing is, and the crystal is plate-shaped; the smaller D (010) is, it indicates that the growth of the crystal b axis is limited, and the crystal grows along the ac crystal plane. Since lithium ions diffuse along the b axis, it is beneficial to shorten the diffusion channel of lithium ions and improve conductivity. The value of D (010) of the present invention satisfies 4 ≤D(010)≤9 In theory, the smaller the D(010), the better the electrochemical performance of the material. However, if D(010) is too small, it is not only difficult to achieve in technology, but also the plate-like crystals are easily broken during the preparation of the electrode or in use, resulting in unstable performance and easy puncture of the diaphragm. The value satisfies 4 ≤D(010)≤6 .

[0028] The present invention limits the crystal structure factor A of the lithium iron phosphate positive electrode material to 4.600. -4 ≤A≤9.500 -4 The lithium iron phosphate positive electrode material has excellent low-temperature electrochemical performance, wherein the low-temperature electrochemical performance is related to the lithium ion diffusion rate of lithium iron phosphate at low temperature.

[0029] In other embodiments of the present invention, the value of the crystal structure factor A can be, for example, 4.600. -4 , 5.200 -4 , 5.800 -4 , 6.800 -4 , 7.500 -4 , 8.500 -4 , 9.000 -4 , 9.500 -4 The value of crystallinity C can be, for example, any one of 0.0900, 0.1000, 0.1100, 0.1200, or any range between two thereof. The value of unit cell volume V can be, for example, 290 , 291 , 292 Any one of them or a range between any two of them. D(010) can take a value of, for example, 4 , 5 , 6 , 7 , 8 , Any one of them or the range between any two.

[0030] Furthermore, the matrix formula is as follows: Li 1-x A x Fe 1-y M y (PO 4-z )D z, wherein A is selected from at least one of Na and Mg; M is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; D is selected from at least one of F, S, N and Cl; 0≤x≤0.1; 0≤y≤0.1 and 0≤z≤0.1. By doping with A source, D source or / and M source, various properties of lithium iron phosphate can be improved, including electrochemical properties, hardness, morphology, particle size and its distribution.

[0031] Furthermore, the mass of the carbon coating layer is 0.5% to 5%, preferably 1.1% to 1.5%, of the mass of the lithium iron phosphate positive electrode material.

[0032] In addition, the present invention also provides a typical but non-limiting method for preparing the above-mentioned lithium iron phosphate positive electrode material, which comprises the following steps: S1. Stir and react a mixture of lithium carbonate, a divalent iron source, a phosphorus source and an ethylene glycol compound solution to obtain a precursor suspension.

[0033] Wherein, the divalent iron source includes but is not limited to at least one of ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous oxalate and ferrous acetate; the phosphorus source includes but is not limited to at least one of phosphoric acid, sodium dihydrogen phosphate, sodium monohydrogen phosphate, ammonium dihydrogen phosphate and ammonium monohydrogen phosphate; the ethylene glycol compound refers to a water-soluble compound containing an ethylene glycol structure in the molecular structure, and further, the ethylene glycol structure refers to OH-C=C-OH; the ethylene glycol compound includes but is not limited to at least one of 1,2-ethylene glycol, squaric acid, crotonic acid, sodium crotonate, 2,3-dihydroxycyclopent-2-ene-1-one, 2,3-dihydroxy-4-(hydroxymethyl)cyclopent-2-ene-1-one and 3,4-dihydroxy-5-methyl-2-furanone. The mass percentage content of the ethylene glycol compound in the ethylene glycol compound solution is 5% to 20%, and the solvent is water.

[0034] In the present invention, the reaction pH of the mixture for stirring reaction is 1 to 2.5, the reaction temperature is 80 to 90 ° C, the reaction time is 1 to 4 hours, and the stirring speed is 300 to 800 rpm. After the stirring reaction is completed, the temperature is lowered to 10 to 25 ° C, and stirred until no bubbles are generated. In other embodiments of the present invention, the pH of the stirring reaction can be, for example, any one of 1, 1.5, 2, and 2.5, or a range value between any two of them, the reaction temperature can be, for example, any one of 80 ° C, 82 ° C, 85 ° C, 88 ° C, and 90 ° C, or a range value between any two of them, the reaction time can be, for example, any one of 1h, 2h, 3h, and 4h, or a range value between any two of them, and the stirring speed can be, for example, any one of 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, and 800rpm, or a range value between any two of them.

[0035] In the present invention, lithium carbonate is used as a lithium source and mixed with a divalent iron source, a phosphorus source, and an ethylene glycol compound solution, and stirred to react at a relatively low temperature (80-90°C) and a low pH value (1-2.5). Phosphate in the phosphorus source reacts with divalent iron ions to form an unstable ferrous phosphate precipitate (precipitation-dissolution is performed simultaneously), and lithium carbonate reacts with an acid to release Li + and carbon dioxide gas, thereby forming tiny bubbles, the collapse of which can lead to the precipitation of ions (Fe 2+ , Li + PO4 3- ) local supersaturation, promote the primary nucleation of lithium iron phosphate precipitation, thereby shortening the time of the hydrothermal reaction and reducing the temperature of the hydrothermal reaction; the ethylene glycol compound also acts as an antioxidant and chelating agent for divalent iron ions, and the ethylene glycol compound can prevent the oxidation of divalent iron ions to trivalent iron ions during the stirring reaction; compared with saturated polyols (such as ethylene glycol in the prior art), the ethylene glycol compound has a stronger chelating effect on divalent iron ions due to the hydroxyl group connected to the unsaturated carbon atom, and thus has a more obvious effect on slowing down the crystal growth rate, thereby greatly improving the crystallinity; in addition, since the water solubility of the ethylene glycol compound is lower than that of saturated polyols such as ethylene glycol, it is more inclined to chelate with divalent iron ions and thus adsorb on the crystal surface to achieve the effect of regulating the crystal morphology.

[0036] Furthermore, a doping element M source may be added to the mixture, and the M source includes a water-soluble salt of at least one element selected from the group consisting of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y.

[0037] As a preferred preparation method of the present invention, firstly, a divalent iron source and an M source are dissolved in an ethylene glycol compound solution to form a metal salt solution; a phosphorus source is dissolved in water to form a phosphorus source solution; lithium carbonate is dispersed in the metal salt solution to obtain a dispersion, and then the phosphorus source solution is added to obtain a mixture.

[0038] Preferably, the molar concentration of the metal element in the metal salt solution is 0.8-1.5 M, and the ratio of the divalent iron source and the M source in the metal salt solution is based on the matrix formula Li 1-x A x Fe 1-y M y (PO 4-z )D z The ratio of iron element and M element is used for feeding.

[0039] Preferably, the molar concentration of the phosphorus source in the phosphorus source solution is 0.85-3M, and the ratio of the total molar amount of the divalent iron source and the M source to the molar amount of the phosphorus source is 1:1.05-1.5.

[0040] Preferably, the ratio of the total molar amount of the divalent iron source and the M source to the molar amount of the lithium element in the lithium carbonate is 1:1.01-1.1.

[0041] S2. subjecting the precursor suspension to a hydrothermal reaction and solid-liquid separation to obtain a solid precursor.

[0042] The conditions of the hydrothermal reaction in the process of preparing the solid precursor are: temperature of 160-200°C, time of 1-3h, and stirring rate of 100-300rpm. In other embodiments of the present invention, the temperature of the hydrothermal reaction can be, for example, any one of 160°C, 170°C, 180°C, 190°C, 200°C, or a range value between any two thereof, the time can be any one of 1h, 2h, 3h, or a range value between any two thereof, and the stirring rate can be any one of 100rpm, 200rpm, 300rpm, or a range value between any two thereof.

[0043] During the hydrothermal reaction, the chelating effect of the ethylene glycol compound on the divalent iron ions can, on the one hand, reduce the diffusion rate of the divalent iron ions, inhibit the orderly arrangement of the ions, and thus slow down the crystal growth rate, thereby obtaining lithium iron phosphate crystals with higher crystallinity; on the other hand, the ethylene glycol compound combines with the divalent iron ions arranged on the (010) crystal plane of the lithium iron phosphate and adsorbs on the crystal plane, inhibiting the growth of the crystal plane, thereby obtaining lithium iron phosphate crystals with a (010) crystal plane orientation.

[0044] S3. After mixing and drying the solid precursor and the carbon source, calcining is performed under an inert atmosphere to obtain a lithium iron phosphate positive electrode material.

[0045] The mass ratio of the solid precursor to the carbon source is 1:0.04-0.1; the carbon source is selected from at least one of glucose, starch, phenolic resin, sucrose, cellulose, polyethylene glycol and citric acid; during the mixing process, a doping element A source and / or D source may be added, the A source is selected from at least one of magnesium fluoride, sodium fluoride, sodium chloride and sodium sulfide; the D source is selected from at least one of potassium fluoride, magnesium fluoride, sodium fluoride, ammonium fluoride, lithium fluoride, melamine, amino acid, thiocyanate, thiourea, sulfur, sodium sulfide, ammonium sulfide, sodium chloride, ammonium chloride, lithium chloride and urea; The purpose of calcination is to further improve the crystallinity of lithium iron phosphate and introduce a carbon coating layer to improve the conductivity. The calcination temperature is 550~650℃ and the calcination time is 4~8h.

[0046] The preparation method of the lithium iron phosphate positive electrode material provided by the present invention can prepare D(010) in the preferred range (4 ~6 ), lithium iron phosphate positive electrode material with high crystallinity. However, it does not have D(010) in the preferred range but satisfies 4.600 -4 ≤A≤9.500 -4 The lithium iron phosphate positive electrode material also has good electrochemical properties, so it is not necessary to use the preparation method provided by the present invention to prepare a product that can solve the technical problem.

[0047] The lithium iron phosphate positive electrode material can be widely used in the preparation of batteries, and the prepared batteries have excellent electrochemical performance. In this regard, the present invention also provides a lithium ion battery, which includes the lithium iron phosphate positive electrode material.

[0048] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0049] The present invention provides lithium iron phosphate positive electrode materials as shown in Table 1 and Table 2, and performs X-ray diffraction (XRD) test, chemical composition analysis, tap density, specific surface area and particle size test on the materials.

[0050] Among them, the detection method is as follows: (1) XRD: X-ray powder diffractometer (XRD, Rigaku D / max-2600PC) was used to study the crystal phase and crystal structure of the material. Cu Kα rays were used for testing, with a wavelength of λ of 0.154056nm, a voltage of 40kV, a current of 40mA, and a scanning range of 2θ of 10~80°. The XRD test results were analyzed using Jade 6 software, and the full spectrum was fitted and refined. wp ≤10%(R wp is the residual variance factor of the weighted graph, which can ensure the precision of refinement).

[0051] (2) Chemical composition analysis was performed using PE Avio200 inductively coupled plasma optical emission spectroscopy (ICP-OES).

[0052] (3) Tap density TD: measured in accordance with GB / T 21354-2008 method for measuring tap density of powder products.

[0053] (4) BET determination of specific surface area: According to GB / T 21650.2-2008 "Determination of pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method Part 2: Analysis of mesopores and macropores by gas adsorption method". The powdered sample was tested using Autosorb IQ2 fully automatic specific surface area pore size analyzer to obtain nitrogen adsorption and desorption curves. The temperature condition was a constant temperature of -196°C and the pressure condition was from 0.005MPa to 0.100MPa. The data in the medium and low pressure stages were processed and calculated using the BET formula to obtain the specific surface area.

[0054] (5) Particle size Dv (50): tested using MS3000 laser particle size analyzer.

[0055] Please refer to Table 1 and Table 2 for the test results.

[0056] Table 1. Statistics of crystal structure test results of different materials

[0057] Figure 1 XRD of lithium iron phosphate positive electrode materials prepared in Example 3, Example 5, Comparative Example 1 and Comparative Example 2, and magnified images of diffraction peaks of (010) and (311) crystal planes. Comparison with the standard card shows that the present invention successfully synthesized LiFePO4. In addition, the diffraction peaks of (010) and (311) crystal planes were analyzed and calculated according to the method described in the present invention to obtain the crystal structure factor A.

[0058] Figure 2 The SEM images of the lithium iron phosphate positive electrode materials prepared in Example 3 (A) and Comparative Example 1 (B) are shown. As can be seen from the figure, Example 3 has a flake morphology, and Comparative Example 2 has an irregular particle morphology. The morphologies of the two are consistent with the D (010) obtained by the test, indicating that Example 3 has a (010) crystal plane orientation.

[0059] Table 2. Statistical table of composition and performance test results of different samples

[0060] Electrochemical testing was performed on the lithium iron phosphate positive electrode materials provided in the above examples and comparative examples.

[0061] Battery assembly: According to the mass ratio of positive electrode material: acetylene black: PVDF of 75:15:10, a uniform slurry is prepared and evenly coated on an aluminum foil substrate as the positive electrode of the simulated battery. The negative electrode of the simulated battery uses a lithium sheet, a polypropylene porous membrane is used as a separator, and the electrolyte is 1 mol LiPF6 dissolved in a mixed solvent of 1L EC and DMC (volume ratio 1:1). The positive electrode, negative electrode, electrolyte, and separator are assembled into a battery in an argon-protected glove box.

[0062] Electrochemical performance at room temperature: After charging and discharging at a rate of 0.1C for one week at 25°C, the 0.1C discharge capacity (25°C) was obtained; then the charge and discharge cycle performance test was carried out at a rate of 1C (200 weeks), and the 1C discharge capacity (25°C) in the first week and the 1C discharge capacity (25°C) in the 200th week were obtained, and the capacity retention rate was calculated based on this.

[0063] Low temperature electrochemical performance includes low temperature discharge rate and low temperature DCR growth rate.

[0064] Low temperature DCR growth rate test: After charging and discharging at a rate of 0.1C for one week at 25°C, the charge and discharge cycle performance test (200 weeks) was performed at a rate of 1C at -10°C. Among them, DCR growth rate = (200th week DCR value - 1st week DCR value) ÷ 1st week DCR value × 100%; DCR value = (1C static voltage before discharge - 1C voltage after 10s discharge) ÷ 1C constant current.

[0065] Low temperature discharge rate test: After charging and discharging for one cycle at a rate of 0.1C at 25°C, charge at 0.5C to 3.8V and record the charging capacity (i.e. 0.5C charging capacity); at -10°C, discharge at a constant current of 1C to 2.0V and record the discharge capacity (i.e. 1C discharge capacity).

[0066] Low temperature discharge rate = (1C discharge capacity ÷ 0.5C charging capacity) × 100%.

[0067] The charge and discharge voltage range is 2 to 3.8 V.

[0068] Table 3. Electrochemical performance test statistics of different samples

[0069] It can be seen from Table 1, Table 2 and Table 3 that the crystal structure factors A and D (010) of Examples 1-8 provided by the present invention all meet the standard defined by the present invention (4.600 -4 ≤A≤9.500 -4 And 4 ≤D(010)≤9 ), while the crystal structure factors A in Comparative Examples 1-3 do not meet the standards defined in the present invention.

[0070] Correspondingly, it can be seen from the data of Examples 1-8 and Comparative Examples 1-3 that when the positive electrode materials have similar TD, BET, and Dv(50), but different crystal structure factors A, the electrochemical properties of the materials are different, and the difference in low-temperature electrochemical performance is greater. Specifically, the larger the value of the crystal structure factor, the better the low-temperature electrochemical performance of the positive electrode material. Although the electrochemical performance at room temperature is also improved, the change is not as good as the low-temperature electrochemical performance. The specific reason is that it is not enough to provide Li at low temperatures. + The activation energy of deintercalation and insertion is low, so the low-temperature electrochemical performance of lithium iron phosphate is generally low. However, the present invention adjusts the crystal structure of the lithium iron phosphate positive electrode material to meet the standard defined in the present invention (4.600 -4 ≤A≤9.500 -4 And 4 ≤D(010)≤9 ), the Li iron phosphate cathode material Li + The shortened diffusion path is beneficial to increase the Li + The deintercalation efficiency is improved, thereby improving the low-temperature performance, while the effect on the room-temperature electrochemical performance is not obvious by adjusting the crystal structure factor, because sufficient Li + From the above electrochemical performance test results, it can be seen that when the crystal structure factors A and D (010) of the lithium iron phosphate positive electrode material meet the limited range of the present invention (4.600 -4 ≤A≤9.500 -4 And 4 ≤D(010)≤9 ), good electrochemical performance can be obtained. Even if the range of D(010) in Examples 2, 5 and 8 satisfies 4 ≤D(010)≤9 , but does not meet the preferred range 4 ≤D(010)≤6 In Example 8, the crystallinity C does not satisfy 0.0900≤C≤0.1200, and the unit cell volume V does not satisfy 290 ≤V≤292 , and also have good electrochemical performance. However, comparative examples 1-3 do not meet the limited scope of the present invention, and at this time, their electrochemical performance is significantly worse than that of the above examples.

[0071] Specifically, the crystal structure factors of Comparative Examples 1 and 2 are lower than 4.6 -4 The crystallinity of comparative example 1 is lower than 0.09, and the D(010) of comparative example 2 is higher than 9. , which greatly reduces the low-temperature electrochemical performance of Comparative Examples 1-2, but the room-temperature electrochemical performance of Comparative Example 2 is still at an average level, indicating that crystallinity has a great influence on the room-temperature electrochemical performance of the positive electrode material. However, the crystallinity, unit cell volume and D(010) of Comparative Example 3 are all within the scope of the present invention, but the crystal structure factor is lower than 4.6 -4 This proves that the positive electrode material does not have good electrochemical performance just because the crystallinity, unit cell volume and D(010) are within the limited range. The crystal structure factor A must be within the limited range.

[0072] In addition, the present invention also provides corresponding preparation methods of the above product embodiments and product comparison examples.

[0073] Method Example 1 This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, and the product obtained by the preparation corresponds to the product of the above-mentioned embodiment 1 (the matrix molecular formula is Li[Fe 0.988 Ti 0.012 ]PO4), the preparation method of this embodiment comprises the following steps: (1) Dissolve ferrous sulfate heptahydrate and titanyl sulfate in an aqueous solution of 1,2-ethylene glycol to form a metal salt solution; and dissolve phosphoric acid in water to form a phosphorus source solution.

[0074] The molar concentration of the metal element in the metal salt solution is 1.2M, the mass percentage concentration of the 1,2-ethylene glycol compound in the aqueous solution of 1,2-ethylene glycol is 13wt%; the ratio of ferrous sulfate heptahydrate and titanyl sulfate is n(Fe):n(Ti)=0.988:0.012.

[0075] The concentration of the phosphorus source solution is 2M, and the ratio of the total molar amount of the iron element and the Ti element to the molar amount of the phosphorus element is 1:1.22.

[0076] (2) Ultrasonic dispersion of lithium carbonate with a particle size of 300-500 mesh in a metal salt solution to obtain a dispersion, then adding a phosphorus source solution and stirring to dissolve, adding ammonia water to adjust the solution pH to 1.8, and then stirring to react at a reaction temperature of 90°C, a reaction time of 2h, and a stirring speed of 500rpm. After the reaction is completed, the temperature is lowered to 20°C and ultrasonicated for 30min to obtain a precursor suspension.

[0077] The ratio of the total molar amount of iron element and Ti element to the molar amount of lithium element in the feed amount of lithium carbonate is 1:1.05.

[0078] (3) The precursor suspension was subjected to a hydrothermal reaction at a temperature of 200°C, a time of 3 hours, and a stirring rate of 180 rpm. After the reaction was completed, the reaction solution was concentrated, cooled to room temperature, and then solid-liquid separation was performed. The obtained solid was washed with deionized water and cleaned to obtain a solid precursor.

[0079] (4) The solid precursor and glucose are ball-milled with ethanol as a dispersant, and the mass ratio of the solid precursor to the carbon source is 1:0.07. The mixture is then heat-dried and calcined at 600°C for 6 h in a nitrogen atmosphere. After crushing and screening, a lithium iron phosphate positive electrode material is obtained.

[0080] Method Example 2 This embodiment provides a method for preparing lithium iron phosphate positive electrode material by carbon reduction method, and the product obtained by the preparation corresponds to the product of the above embodiment 2 (the matrix molecular formula is Li[Fe 0.988 Ti 0.012 ]PO4), which comprises the following steps: (1) According to the molar ratio of n(Fe):n(Ti)=0.988:0.012, a certain amount of ferrous sulfate heptahydrate and titanyl sulfate were weighed and dissolved in deionized water to prepare a 2M mixed salt solution; a certain amount of phosphoric acid was weighed and mixed with water to obtain a phosphoric acid solution with a phosphate ion concentration of 2M.

[0081] (2) A mixed salt solution, a phosphoric acid solution, a 0.6 M hydrogen peroxide solution, and a 2 M ammonia solution were added to the reactor in parallel using a constant flow pump. The flow rates of the mixed salt solution, phosphoric acid solution, and hydrogen peroxide solution were all 120 mL / h. The flow rate of ammonia solution was controlled to maintain the pH of the reaction solution at 1.2±0.1. The temperature was controlled to maintain at 60°C during the reaction. The reaction time was 2 h and the stirring speed was 600 rpm. After the reaction was completed, the mixture was filtered and washed with deionized water to obtain an amorphous precipitate (wet material, solid content of 85.22%). (3) The amorphous precipitate is uniformly dispersed in the aging solution to undergo an aging-transformation reaction. After the reaction is completed, the precipitate is filtered and washed with deionized water. The filter residue is spray-dried to obtain a crystalline precipitate.

[0082] The aging solution is a phosphoric acid aqueous solution in which 1,2-ethylene glycol is dissolved, the pH is 2, and the concentration of 1,2-ethylene glycol is 15wt%. The feeding ratio of amorphous precipitate to aging solution is 1g:200mL; the aging crystallization reaction conditions are: temperature 90°C, time 2h, and stirring rate 200rpm.

[0083] (4) The crystalline precipitate was calcined at a temperature of 700°C, a heating rate of 4°C / min, and a calcination time of 2 h to obtain a titanium-doped iron phosphate precursor.

[0084] (5) The titanium-doped iron phosphate precursor was mixed with lithium carbonate, glucose and ethanol in a molar ratio of n(precursor): n(Li): n(glucose) = 1:1.04:0.07, and the mixed material was placed in a grinder for grinding for 6 hours to obtain a slurry, which was placed in a vacuum oven at 80°C and dried for 4 hours to obtain a dry material; the dry material was calcined at 750°C under a nitrogen atmosphere for 9 hours, and after crushing and screening, a lithium iron phosphate positive electrode material was obtained.

[0085] Method Examples 3-4 and 6-7 The preparation methods of method examples 3-4 and 6-7 are the same as those of example 1, except that the parameters in the preparation process are different. The products prepared in method examples 3-4 and 6-7 correspond to the products of the above examples 3-4 and 6-7, respectively. Specifically, the preparation parameters are shown in Table 4: Table 4. Preparation parameter statistics

[0086] Method Example 5 This embodiment provides a method for preparing a lithium iron phosphate positive electrode material by using a carbon reduction method. The product obtained by the method corresponds to the product of the above-mentioned embodiment 5 (the matrix molecular formula is LiFePO4), and the method comprises the following steps: (1) Weigh ferrous sulfate heptahydrate and dissolve it in water to prepare a 2 M salt solution; weigh a certain amount of phosphoric acid and mix it with water to prepare a phosphoric acid solution with a phosphate ion concentration of 2 M.

[0087] (2) A salt solution, a phosphoric acid solution, a 0.6 M hydrogen peroxide solution, and a 2 M ammonia solution were added to the reactor in parallel using a constant flow pump. The flow rates of the salt solution, phosphoric acid solution, and hydrogen peroxide solution were all 120 mL / h. The flow rate of the ammonia solution was controlled to maintain the pH of the reaction solution at 1.2±0.1. The temperature was controlled to maintain at 60°C during the reaction. The reaction time was 2 h and the stirring speed was 600 rpm. After the reaction was completed, the mixture was filtered and washed with deionized water to obtain an amorphous precipitate (wet material, solid content of 89.57%). (3) The amorphous precipitate is uniformly dispersed in the aging solution to undergo an aging-transformation reaction. After the reaction is completed, the precipitate is filtered and washed with deionized water. The filter residue is spray-dried to obtain a crystalline precipitate.

[0088] The aging solution is a phosphoric acid aqueous solution in which 1,2-ethylene glycol is dissolved, the pH is 2, and the concentration of 1,2-ethylene glycol is 20wt%. The feeding ratio of amorphous precipitate to aging solution is 1g:200mL; the aging crystallization reaction conditions are: temperature 90°C, time 2h, and stirring rate 200rpm.

[0089] (4) The crystalline precipitate is calcined at a temperature of 700°C, a heating rate of 4°C / min, and a calcination time of 2 h to obtain an iron phosphate precursor.

[0090] (5) The iron phosphate precursor, lithium carbonate, glucose and ethanol were mixed in a molar ratio of n(precursor): n(Li): n(glucose) = 1:1.04:0.06, and the mixed material was placed in a grinder for grinding for 6 hours to obtain a slurry, which was placed in a vacuum oven at 80°C and dried for 4 hours to obtain a dry material; the dry material was calcined at 750°C under a nitrogen atmosphere for 9 hours, and after crushing and screening, a lithium iron phosphate positive electrode material was obtained.

[0091] Method Example 8 This embodiment provides a method for preparing a lithium iron phosphate positive electrode material by using a carbon reduction method. The product obtained by the method corresponds to the product of the above-mentioned embodiment 8 (the matrix molecular formula is LiFePO4), which comprises the following steps: The difference from Example 5 is that in step (3), 1,2-ethylene glycol is replaced by squaric acid; the calcination temperature in step (4) is 600° C. and the heating rate is 2° C. / min.

[0092] Method Comparative Example 1 This comparative example provides a method for preparing a lithium iron phosphate positive electrode material by a solvothermal reaction, wherein the product obtained by the preparation corresponds to the product of the comparative example 1 above (the matrix molecular formula is LiFePO4), and comprises the following steps: (1) Weigh ferrous sulfate heptahydrate and dissolve it in ethylene glycol to prepare a 0.1 g / mL iron salt solution; weigh lithium hydroxide monohydrate and dissolve it in ethylene glycol to prepare a 0.04 g / mL lithium source solution.

[0093] (2) Add 2.8 mL of 85 wt% phosphoric acid to 90 mL of lithium source solution, stir for 30 min, then add iron salt solution and continue stirring for 30 min to obtain a precursor suspension.

[0094] (3) The precursor suspension is placed in an oven at 180°C for a solvothermal reaction for 10 hours. After solid-liquid separation, the obtained solid is washed and dried to obtain lithium iron phosphate LiFePO4.

[0095] (4) Lithium iron phosphate LiFePO4 and glucose are mixed in a mass ratio of 1:0.07, ball-milled with ethanol as a dispersant, and then heat-dried and calcined at 600°C for 6 h in a nitrogen atmosphere. After crushing and screening, lithium iron phosphate positive electrode material is obtained.

[0096] Method Comparative Example 2 This comparative example provides a method for preparing a lithium iron phosphate positive electrode material by a solid phase synthesis method. The product obtained by the solid phase synthesis method corresponds to the product of the comparative example 2 above (the matrix molecular formula is LiFePO4), which comprises the following steps: (1) Lithium phosphate, ferrous oxalate dihydrate and ammonium hydrogen phosphate were weighed according to the stoichiometric ratio of 1:3:3, ball-milled for 6 h with ethanol as a dispersant and dried to obtain a precursor; the precursor was calcined at 500°C for 12 h, and after cooling, crushed and sieved to obtain lithium iron phosphate LiFePO4.

[0097] (2) Lithium iron phosphate LiFePO4 and glucose are mixed in a mass ratio of 1:0.07, ball-milled with ethanol as a dispersant, and then heat-dried and calcined at 600°C for 2h in a nitrogen atmosphere. After crushing and sieving, lithium iron phosphate positive electrode material is obtained.

[0098] Method Comparative Example 3 This comparative example provides a method for preparing a lithium iron phosphate positive electrode material by solvothermal reaction, wherein the product obtained by the preparation corresponds to the product of the comparative example 3 above (the matrix molecular formula is LiFePO4,), and comprises the following steps: (1) Dissolve 1,2-ethylene glycol in ethylene glycol to prepare a mixed solvent with a mass percentage concentration of 10% of 1,2-ethylene glycol; weigh ferrous sulfate heptahydrate and dissolve it in the mixed solvent to prepare a 0.1 g / mL iron salt solution; weigh lithium hydroxide monohydrate and dissolve it in the mixed solvent to prepare a 0.04 g / mL lithium source solution.

[0099] (2) Add 2.8 mL of 85 wt% phosphoric acid to 90 mL of lithium source solution, stir for 30 min, then add iron salt solution and continue stirring for 30 min to obtain a precursor suspension.

[0100] (3) The precursor suspension is placed in an oven at 200°C for a solvothermal reaction for 10 hours. After solid-liquid separation, the obtained solid is washed and dried to obtain lithium iron phosphate LiFePO4.

[0101] (4) Lithium iron phosphate LiFePO4 and glucose are mixed in a mass ratio of 1:0.07, ball-milled with ethanol as a dispersant, and then heat-dried and calcined at 600°C for 6 h in a nitrogen atmosphere. After crushing and screening, lithium iron phosphate positive electrode material is obtained.

[0102] Combining the products and preparation methods of the present invention, as well as the performance of the products in Tables 1 to 4 above, it can be seen that Example 1 and Example 2 have the same chemical composition, but due to their different preparation methods, the performance of Example 1 is different. In the preferred range, while Example 2 is not in the preferred range, at this time, the value of the crystal structure factor of Example 2 is lower than that of Example 1. Similarly, in Examples 3-5, the value of the crystal structure factor of Example 3-4 obtained by the preparation method of the present invention is greater than that of Example 5. It is fully proved that the preparation method provided by the present invention can prepare a lithium iron phosphate positive electrode material with D(010) in the preferred range and high crystallinity. However, it does not have D(010) in the preferred range but meets 4.600 -4 ≤A≤9.500 -4 The lithium iron phosphate positive electrode material also has good electrochemical properties, so it is not necessary to use the preparation method provided by the present invention to prepare a product that can solve the technical problem.

[0103] In addition, the present invention also provides method examples 9-16 and method comparative examples 4-5. Method examples 9-16 and method comparative examples 4-5 perform single factor variable analysis on a certain parameter of method example 1.

[0104] Specifically, the specific steps of method examples 9-16 and method comparative examples 4-5 are as follows: Method Example 9 This embodiment is substantially the same as method embodiment 1, except that the mass percentage concentration of 1,2-ethylene glycol compound in the aqueous solution of 1,2-ethylene glycol in this embodiment is 5 wt %.

[0105] Method Example 10 This embodiment is substantially the same as method embodiment 1, except that the mass percentage concentration of 1,2-ethylene glycol compound in the aqueous solution of 1,2-ethylene glycol in this embodiment is 20 wt %.

[0106] Method Example 11 This embodiment is substantially the same as method embodiment 1, except that the ethylene glycol compound in this embodiment is squaric acid.

[0107] Method Example 12 This embodiment is substantially the same as method embodiment 1, except that the ethylene glycol compound in this embodiment is sodium crotonate.

[0108] Method Example 13 This embodiment is substantially the same as method embodiment 1, except that the pH of the stirring reaction in this embodiment is 1.

[0109] Method Example 14 This embodiment is substantially the same as method embodiment 1, except that the pH of the stirring reaction in this embodiment is 2.5.

[0110] Method Example 15 This embodiment is substantially the same as method embodiment 1, except that the rotation speed of the stirring reaction in this embodiment is 300 rpm.

[0111] Method Example 16 This embodiment is substantially the same as method embodiment 1, except that the rotation speed of the stirring reaction in this embodiment is 800 rpm.

[0112] Method Comparative Example 4 This comparative example is substantially the same as Example 1, except that, in this comparative example, 1,2-ethylene glycol in Example 1 is replaced by ethylene glycol.

[0113] Method Comparative Example 5 This comparative example is substantially the same as Example 1, except that, in this comparative example, the lithium carbonate in Example 1 is replaced by lithium hydroxide.

[0114] The performance of the lithium iron phosphate positive electrode materials prepared by the above method examples 9-16 and method comparative examples 4-5 was tested. Please refer to Tables 5 and 6 for the test results.

[0115] Table 5. Statistics of crystal structure test results of different samples

[0116] Table 6. Statistical table of composition and performance test results of different samples

[0117] As can be seen from the above table, method examples 9 to 16 and method comparative examples 4 and 5 are single factor variable analyses of method example 1. From the results of method examples 9 to 16 and method comparative examples 4 to 5, it can be seen that the crystal structure of the positive electrode material with the same chemical composition can be regulated by the preparation method.

[0118] Specifically, the amount and type of the ethylene glycol compound added in method examples 9 to 12 were changed. It can be seen that the amount and type of the ethylene glycol compound added have an effect on the crystal structure factor of lithium iron phosphate. The crystal structure factor increases first and then decreases with the increase in the amount of ethylene glycol compound added. Due to the excessive amount of addition, the free Fe 2+ Reduce, reduce its saturation, resulting in limited nucleation of lithium iron phosphate, so the crystallinity is reduced; if the addition amount is too small, it is difficult to play a role in crystal plane regulation, so that the crystal structure factor becomes larger.

[0119] In method examples 13 to 16, the pH and stirring speed during the stirring reaction were changed. It can be seen that the pH and stirring speed during the stirring reaction have an impact on the crystal structure factor of lithium iron phosphate, wherein the crystal structure factor increases first and then decreases with increasing pH, and increases first and then decreases with increasing stirring speed; the pH value and stirring speed are closely related to the dissolution rate of lithium carbonate (i.e., the production of carbon dioxide gas). If the production rate of carbon dioxide is too fast, it will lead to uneven distribution of various elements, and nucleation defects will easily occur, thereby affecting the crystallinity; if the production rate of carbon dioxide is too slow, the local supersaturation produced will be low, which will inhibit nucleation.

[0120] In comparative example 4, ethylene glycol is used instead of ethylene glycol compound. From the results, it can be seen that ethylene glycol compound can effectively reduce D(010) of lithium iron phosphate compared with ethylene glycol, and also improve the crystallinity of lithium iron phosphate to a certain extent. Therefore, the crystal structure factor of lithium iron phosphate prepared in the embodiment is larger than that in comparative example 4. The reason is that the hydroxyl group in the ethylene glycol compound is connected by unsaturated carbon, which is connected to Fe 2+ The chelating ability of iodine is greatly improved, so the regulating effect on the crystal surface is greatly improved, and slowing down the crystal growth rate is beneficial to improving the crystallinity.

[0121] In comparative example 5 of the method, lithium hydroxide is used as the lithium source. Compared with the lithium carbonate used as the lithium source in Example 1, the carbon dioxide bubbles generated by lithium carbonate in an acidic environment have a significant promoting effect on the crystallinity of lithium iron phosphate, and also reduce the D(010) of lithium iron phosphate to a certain extent. Therefore, the crystal structure factor of lithium iron phosphate prepared in method example 1 is larger than that in comparative example 5. The reason is that the rupture of tiny bubbles can lead to local supersaturation and promote the primary nucleation of lithium iron phosphate precipitation. Therefore, under the same hydrothermal reaction conditions, the crystallization performance of the obtained lithium iron phosphate is better.

[0122] In summary, the present invention provides a lithium iron phosphate positive electrode material, the crystal structure factor A of which satisfies 4.600 -4 ≤A≤9.500 -4 , and its grain size D(010) satisfies 4 ≤D(010)≤9 , the lithium iron phosphate cathode material that meets the above range has excellent low-temperature electrochemical performance. The crystal structure factor comprehensively evaluates the three indicators of the crystallinity C, unit cell volume V and crystal face (010) grain size D(010) of the lithium iron phosphate cathode material. Among them, the higher the crystallinity, the higher the lithium ion diffusion rate and the better the conductivity; the smaller the unit cell volume, the shorter the lithium ion deintercalation channel, the easier it is to transition, which is beneficial to improve the conductivity of the material and improve the cycle performance; the smaller D(010), the more conducive to shortening the lithium ion diffusion channel and improving the conductivity. In addition, the preparation method of the lithium iron phosphate cathode material provided by the present invention only provides an exemplary preparation method. In the preparation method of the present invention, lithium carbonate is used as a lithium source and mixed with a divalent iron source, a phosphorus source, and an ethylene glycol compound for stirring reaction to obtain a precursor suspension, and the stirring reaction is carried out at a relatively low temperature (80~90°C) and a low pH value (1~2.5). The phosphorus source and the divalent iron ions form an unstable ferrous phosphate precipitate (precipitation-dissolution is carried out simultaneously), and the lithium carbonate reacts with the acid to release Li + and carbon dioxide gas, thereby forming tiny bubbles. The bubble burst can lead to local supersaturation, promoting the primary nucleation of lithium iron phosphate precipitation, thereby shortening the hydrothermal reaction time and reducing the hydrothermal reaction temperature; the ethylene glycol compound also acts as a Fe 2+ The antioxidant and chelating agent, ethylene glycol compound can prevent Fe 2+ Oxidized to Fe 3+ ; During the hydrothermal reaction, ethylene glycol compounds react with Fe 2+ The chelation effect can reduce Fe 2+The diffusion rate of ions is inhibited, thereby slowing down the crystal growth rate and obtaining lithium iron phosphate crystals with higher crystallinity. On the other hand, the ethylene glycol compound and the Fe arranged on the (010) crystal surface of lithium iron phosphate 2+ The hydroxyl group of the ethylene glycol compound is connected to the unsaturated carbon atom, so the ethylene glycol compound has a (010) crystal orientation, which is better than the saturated polyol (such as ethylene glycol in the prior art). 2+ The chelating effect of ethylene glycol is stronger, which has a more obvious effect on slowing down the crystal growth rate, thereby greatly improving the crystallinity; in addition, since the water solubility of ethylene glycol compounds is lower than that of saturated polyols such as ethylene glycol, they are more inclined to react with Fe 2+ Chelation and adsorption on the crystal surface achieve the effect of regulating the crystal morphology. This method can prepare a lithium iron phosphate positive electrode material with D(010) in the preferred range and high crystallinity. However, it does not have D(010) in the preferred range but meets 4.600 -4 ≤A≤9.500 -4 The lithium iron phosphate positive electrode material also has good electrochemical properties, so it is not necessary to use the preparation method provided by the present invention to prepare a product that can solve the technical problem.

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium iron phosphate positive electrode material, characterized in that: It includes a substrate and a carbon coating layer coated on the surface of the substrate, and the crystal structure factor A of the lithium iron phosphate positive electrode material satisfies 4.

600. -4 ≤A≤9.500 -4 , the calculation formula of the crystal structure factor A is: A= , Wherein, C refers to the crystallinity of the lithium iron phosphate positive electrode material, which is measured by the ratio of the XRD diffraction peak intensity of the crystal plane (311) to the integrated area of ​​the diffraction peak; V refers to the unit cell volume of the lithium iron phosphate positive electrode material, unit 3 ; Refers to the crystal surface of the lithium iron phosphate positive electrode material The grain size, unit , the value satisfies 4 ≤ ≤9 .

2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The lithium iron phosphate positive electrode material satisfies at least one of the following characteristics (1) to (3): Feature (1): The value satisfies 4 ≤ ≤6 ; Feature (2): The value of C satisfies 0.0900≤C≤0.1200; Feature (3): The value of V satisfies 290 ≤V≤292 .

3. The lithium iron phosphate positive electrode material according to any one of claims 1 to 2, characterized in that The general formula of the matrix is ​​as follows: Li 1-x A x Fe 1-y M y (PO 4-z )D z , wherein A is selected from at least one of Na and Mg; M is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; D is selected from at least one of F, S, N and Cl; 0≤x≤0.1; 0≤y≤0.1 and 0≤z≤0.

1.

4. The lithium iron phosphate positive electrode material according to any one of claims 1 to 2, characterized in that The mass of the carbon coating layer is 0.5% to 5% of the mass of the lithium iron phosphate positive electrode material.

5. A method for preparing a lithium iron phosphate positive electrode material as claimed in any one of claims 1 to 4, characterized in that: It includes: Stirring a mixture of lithium carbonate, a divalent iron source, a phosphorus source and an ethylene glycol compound solution to react to obtain a precursor suspension; The precursor suspension is subjected to a hydrothermal reaction and solid-liquid separation to obtain a solid precursor; The solid precursor and the carbon source are mixed and dried, and then calcined under an inert atmosphere to obtain a lithium iron phosphate positive electrode material.

6. The method for preparing the lithium iron phosphate positive electrode material according to claim 5, characterized in that: The process of preparing the precursor suspension includes at least one of the features (4) to (9): Feature (4): The divalent iron source is at least one selected from ferrous sulfate, ferrous chloride, ferrous nitrate, ferrous oxalate and ferrous acetate; Feature (5): The phosphorus source is at least one selected from phosphoric acid, sodium dihydrogen phosphate, sodium monohydrogen phosphate, ammonium dihydrogen phosphate and ammonium monohydrogen phosphate; Feature (6): The mass percentage content of the ethylene glycol compound in the ethylene glycol compound solution is 5% to 20%; Feature (7): The ethylene glycol compound refers to a water-soluble compound containing an ethylene glycol structure, and the ethylene glycol compound is selected from at least one of 1,2-ethylene glycol, squaric acid, crotonic acid, sodium crotonate, 2,3-dihydroxycyclopent-2-ene-1-one, 2,3-dihydroxy-4-(hydroxymethyl)cyclopent-2-ene-1-one and 3,4-dihydroxy-5-methyl-2-furanone; Feature (8): The pH of the solution in the stirring reaction is 1-2.5, the reaction temperature is 80-90°C, the reaction time is 1-4h, and the stirring speed is 300-800rpm; Feature (9): After the stirring reaction is completed, the temperature is lowered to 10-25°C and stirred until no bubbles are generated.

7. The method for preparing a lithium iron phosphate positive electrode material according to claim 6, characterized in that: During the preparation of the mixture, an M source is also added, which includes the characteristics ( At least one of (10) to (13): Feature (10): dissolving the divalent iron source and the M source in the ethylene glycol compound solution to form a metal salt solution, dissolving the phosphorus source in water to form a phosphorus source solution; dispersing the lithium carbonate in the metal salt solution to obtain a dispersion, and then adding the phosphorus source solution to obtain the mixture, wherein the molar concentration of the metal element in the metal salt solution is 0.8~1.5M, and the molar concentration of the phosphorus source in the phosphorus source solution is 0.85~3M; Feature (11): The ratio of the total molar amount of the divalent iron source and the M source to the molar amount of the phosphorus source is 1:1.05-1.5; Feature (12): The ratio of the total molar amount of the divalent iron source and the M source to the molar amount of the lithium element in the lithium carbonate is 1:1.01-1.1; Feature (13): The M source includes a water-soluble salt of at least one element selected from the group consisting of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y.

8. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: The conditions of the hydrothermal reaction in the process of preparing the solid precursor are: temperature of 160-200° C., time of 1-3 h, and stirring rate of 100-300 rpm.

9. The method for preparing a lithium iron phosphate positive electrode material according to claim 5, characterized in that: After the solid precursor and the carbon source are mixed and dried, the process of calcining under an inert atmosphere includes at least one of the following features (14) to (17): Feature (14): The mass ratio of the solid precursor to the carbon source is 1:0.04-0.1; Feature (15): The carbon source is selected from at least one of glucose, starch, phenolic resin, sucrose, cellulose, polyethylene glycol and citric acid; Feature (16): The mixing process further includes adding a source A and / or a source D, wherein the source A is selected from at least one of magnesium fluoride, sodium fluoride, sodium chloride and sodium sulfide; and the source D is selected from at least one of potassium fluoride, magnesium fluoride, sodium fluoride, ammonium fluoride, lithium fluoride, melamine, amino acid, thiocyanate, thiourea, elemental sulfur, sodium sulfide, ammonium sulfide, sodium chloride, ammonium chloride, lithium chloride and urea; Feature (17): The calcination includes calcination at 550-650°C for 4-8 hours.

10. A lithium ion battery, characterized in that: It includes the lithium iron phosphate positive electrode material according to any one of claims 1 to 4 or the lithium iron phosphate positive electrode material prepared by the preparation method of the lithium iron phosphate positive electrode material according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery

    CN117865111A

  • Composite lithium supplementing material and preparation method thereof, positive electrode material and secondary battery

    CN118039906A

  • Method for producing lithium iron phosphate particle and lithium iron phosphate particle

    JP2011001242A

Cited By

  • Organic framework in-situ derived low-energy-gap lithium iron phosphate material and application thereof

    CN120709334A

  • Lithium iron phosphate positive electrode material and preparation method therefor, and lithium-ion battery

    EP4790763A1

  • Lithium iron phosphate positive electrode material and preparation method therefor, and lithium-ion battery

    WO2026113369A1